The effect of diesel/biodiesel blend ratio on physical-chemical properties of biodiesel - Ying, C. Z.; Maniam, Gaanty Pragas; Nurliyana, Moh Hussin; S. N. M., Khazaai (Penerbit Universiti Malaysia Pahang, 2023)
Biodiesel is a highly sustainable alternative to alleviate fossil fuel shortages and environmental concerns. Many countries have adopted the practice of blending biodiesel into diesel at specific ratios. This study focused on the effect of different biodiesel-diesel blend ratio in terms of acid value, saponification value, peroxide value, and iodine value, and analysed by using Ultraviolet-Visible (UV-Vis) spectroscopy. A series of diesel-biodiesel blends of B20, B40, B60, and B80 were prepared by mixing the biodiesel produced by refined, bleached, and deodorized palm oil through transesterification reaction with pure diesel. Based on the result, the FTIR spectrum showed a slight change in intensity and wavenumber for some possible functional groups but retained the same main characteristic peaks such as C=O, C-O, and OCH3. Predominant compound in biodiesel is oleic acid. Furthermore, acid value, saponification value, iodine value, and peroxide value increased from Euro 5 (B7) to B80 with linear regression (R2) of 0.9817, 0.9971, 0.7521, and 0.9911, respectively. The absence of aromatic compounds in biodiesel causes a decrease in the absorbance of UV light from Euro 5 to B80. Yet, tested parameters were positively accepted according to ASTM - D6751 standard method. Hence, determining the physicochemical properties of blend ratio is vital for industries to counter false claims economically and effectively.